An updated meta-analysis of Chinese herbal medicine for the prevention of COVID-19 based on Western-Eastern medicine - Hu, Siying; Luo, Dan; Zhu, Qikui; Pan, Jie; Chen, Bonan; Furian, Michael; Harkare, Harsh Vivek; Sun, Shoukai; Fansa, Adel; Wu, Xiaoping; Yu, Baili; Ma, Tianhong; et al. (Frontiers in Pharmacology, 2023)
Background and aims: Chinese herbal medicine (CHM) was used to prevent and treat coronavirus disease 2019 (COVID-19) in clinical practices. Many studies have demonstrated that the combination of CHM and western medicine can be more effective in treating COVID-19 compared to western medicine alone. However, evidence-based studies on the prevention in undiagnosed or suspected cases remain scarce. This systematic review and meta-analysis aimed to investigate the effectiveness of CHM in preventing recurrent, new, or suspected COVID-19 diseases. Methods: We conducted a comprehensive search using ten databases including articles published between December 2019 and July 2023 (updated in September 2023). This search aimed to identify studies investigating the use of CHM to prevent COVID-19. Heterogeneity was assessed by a random-effects model. The relative risk (RR) and mean differences were calculated using 95% confidence intervals (CI). The modified Jadad Scale and the Newcastle-Ottawa Scale (NOS) were employed to evaluate the quality of randomized controlled trials and cohort studies, respectively. Results: Seventeen studies with a total of 47,351 patients were included. Results revealed that CHM significantly reduced the incidence of COVID-19 (RR = 0.24, 95% CI = 0.11–0.53, p = 0.0004), influenza (RR = 0.37, 95% CI = 0.18–0.76, p = 0.007), and severe pneumonia exacerbation rate (RR = 0.17, 95% CI = 0.05–0.64, p = 0.009) compared to non-treatment or conventional control group. Evidence evaluation indicated moderate quality evidence for COVID-19 incidence in randomized controlled trials (RCTs) and serum complement components C3 and C4 in RCTs. For the incidence of influenza and severe pneumonia in RCTs as well as the ratio of CD4+/CD8+ lymphocytes, the evidence quality was low. The remaining outcomes including the disappearance rate of symptoms and adverse reactions were deemed to be of very low quality. Conclusion: CHM presents a promising therapeutic option for the prevention of COVID-19. However, additional high-quality clinical trials are needed to further strengthen evidential integrity.